2003
DOI: 10.1111/j.1469-8137.2004.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oxalate formation in Lemna minor: physiological and ultrastructural aspects of high capacity calcium sequestration

Abstract: Summary• The function of calcium oxalate (CaOx) raphide crystal formation, and structural features related to regulation of crystal formation, were studied in Lemna minor fronds using physiological and microscopy techniques.• Specialized crystal-forming cells (crystal idioblasts) increased in number and size; CaOx, but not soluble oxalate, increased in response to increasing calcium in the growth medium. Size and number of idioblasts had a distinct upper limit.• The CaOx crystals are formed in membranous 'cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 68 publications
(127 reference statements)
3
65
0
12
Order By: Relevance
“…These results indicate that the experimental treatments were able to alter plant calcium content. A positive correlation has been found between calcium concentrations in growth medium and the number and size of calcium oxalate crystals in leaves of Pistia stratiotes (Volk et al, 2002), Phaseolus vulgaris (Kuo-Huang and Zindler-Frank, 1998), Lemna minor (Mazen et al, 2004), Corchorus olitorius (Faheed et al, 2013) and Malva parviflora (Faheed et al, 2013). In a study of eddo roots subjected to different calcium concentrations, the number and size of crystals in the root apical zone under 1 mM Ca(NO 3 ) 2 solution were significantly larger than those in 0 mM calcium solution and smaller than those in 15 mM calcium solutions (Islam and Kawasaki, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the experimental treatments were able to alter plant calcium content. A positive correlation has been found between calcium concentrations in growth medium and the number and size of calcium oxalate crystals in leaves of Pistia stratiotes (Volk et al, 2002), Phaseolus vulgaris (Kuo-Huang and Zindler-Frank, 1998), Lemna minor (Mazen et al, 2004), Corchorus olitorius (Faheed et al, 2013) and Malva parviflora (Faheed et al, 2013). In a study of eddo roots subjected to different calcium concentrations, the number and size of crystals in the root apical zone under 1 mM Ca(NO 3 ) 2 solution were significantly larger than those in 0 mM calcium solution and smaller than those in 15 mM calcium solutions (Islam and Kawasaki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with some plant species have shown that the number and/or size of calcium oxalate crystals are positively correlated with the amount of calcium applied to the growth medium (Kuo-Huang and Zindler-Frank, 1998;Volk et al, 2002;Mazen et al, 2004;Faheed et al, 2013). Wu et al (2006) also reported that the average distribution density of calcium oxalate crystals was higher in the leaves of Morus australis Poir grown in a solution containing a high concentration of calcium and no calcium oxalate crystals were found in the leaves of plants grown in a low calcium solution.…”
mentioning
confidence: 99%
“…The number and size of calcium oxalate crystals have been reported to be positively correlated with the amount of calcium supplied in the growth medium (Kuo-Huang and Zindler-Frank, 1998;Volk et al, 2002;Mazen et al, 2004;Faheed et al, 2013). For example, a positive correlation has been observed between calcium concentration in the growth medium and calcium oxalate crystals in the apical zone of primary roots of eddo (Islam and Kawasaki, 2014), and in leaf blades and petioles of eddo (Islam and Kawasaki, 2015).…”
Section: Eddo (Colocasia Esculenta (L) Schott Var Antiquorummentioning
confidence: 99%
“…Observou-se, também, que os CaOx com forma de drusas, presentes principalmente em ectomicorrizas, são maiores que os CaOx do tipo grânulos presentes em raízes não colonizadas ( Figura 1D,H). Borchert (1985) e Mazen et al (2004) relataram que o tamanho e a forma do cristal apresentam grande variação em relação à célula em que se encontra e ao ambiente onde é formado. Também, a quantidade de Ca 2+ e de ácido oxálico disponível, entre outros fatores ambientais, são determinantes para essas características.…”
Section: Microscopia Eletrônica De Varredura Da Superfície Do Mantounclassified